2014
DOI: 10.1007/s00702-014-1304-1
|View full text |Cite|
|
Sign up to set email alerts
|

Neuropathological assessments of the pathology in frontotemporal lobar degeneration with TDP43-positive inclusions: an inter-laboratory study by the BrainNet Europe consortium

Abstract: The BrainNet Europe consortium assessed the reproducibility in the assignment of the type of frontotemporal lobar degeneration (FTLD) with TAR DNA-binding protein (TDP) 43 following current recommendations. The agreement rates were influenced by the immunohistochemical (IHC) method and by the classification strategy followed. p62-IHC staining yielded good uniform quality of stains, but the most reliable results were obtained implementing specific Abs directed against the hallmark protein TDP43. Both assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 41 publications
(85 reference statements)
0
16
0
Order By: Relevance
“…Analysis of formalin-fixed and paraffin-embedded tissue from different parts of the brain was performed, including the frontal cortex (F2), temporal pole cortex, parietal cortex (superior and inferior lobule), occipital pole cortex, amygdala, and the hippocampus, essentially CA1 and entorhinal area of the parahippocampal gyrus. Staging of pathology was evaluated according to a modified assessment of Braak and Alafuzoff and the Aβ staging of Thal [2, 9, 57]. For cases with and without clinical neurological disease, diagnosis was processed identically.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of formalin-fixed and paraffin-embedded tissue from different parts of the brain was performed, including the frontal cortex (F2), temporal pole cortex, parietal cortex (superior and inferior lobule), occipital pole cortex, amygdala, and the hippocampus, essentially CA1 and entorhinal area of the parahippocampal gyrus. Staging of pathology was evaluated according to a modified assessment of Braak and Alafuzoff and the Aβ staging of Thal [2, 9, 57]. For cases with and without clinical neurological disease, diagnosis was processed identically.…”
Section: Methodsmentioning
confidence: 99%
“…Although most FTLD‐TDP cases can easily be assigned to one of the common subtypes (A–D), several studies have found that a minority of cases are difficult to classify; either because the pattern of pathology is felt not to fit with any of the existing subtypes or because it shows overlapping features of more than one subtype . A recent study that evaluated the TDP‐43 pathology in a large series of cases using an unbiased semiquantitative approach found that 19% had the positive pathological features of both type A and type B .…”
Section: Ftld‐tdpmentioning
confidence: 99%
“…Consequently, IHC diagnosis of TDP-43-proteinopathies finds greater concordance among neuropathologists when the anti-phosphorylated-TDP-43 antibody has been applied. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%